Analysis of adolescent girls’ sexual subjectivity - Kajokienė, I. (Psichologija, 2013)
It is difficult to take no notice of the gap existing between the relevance of the theme of sexuality in adolescence for young people themselves and the lack of attention of academia trying to understand, analyze, and conceptualize this experience of young people. There is still a need to understand the profound subjective sexual experience in adolescence, i.e. to reveal the pathways how the feeling that “I am a sexual person” arises in an adolescent’s self-awareness. The aim of the present study was to update and expand the understanding of the phenomenon of the adolescent sexuality experience and to offer an updated model of understanding it, which has been created with reference to adolescents’ narratives. Particularly, it is meant to understand, organize, and analyze a typical, characteristic of the normal development of adolescent girls’ sexual experience, highlighting the discursive position of the subject in order to answer one basic question: how or in what way in the awareness of an adolescent arises the feeling that “I am a sexual person”. The interpretive qualitative study of the exploratory strategy was based on a hermeneutic phenomenological methodological investigator’s position for interpreting the experience of the participants. Data obtained during a semi-structured interview were analyzed using the method of interpretative phenomenological analysis (Smith et al., 2009). The findings have been interpreted in consistence with the paradigm of a positive and normative development of sexuality in adolescence together with some psychoanalytic developmental theories. The study has revealed the typical feelings associated with the regularity of sexual subjectivity emergence in the process of growing self-awareness. The structure of the abstracted meta-theme called “Adolescence sexuality as part of an intensive I–Other experience” is presented to the reader in this publication. The material provides new data on the first conscious sexual experiences of adolescent girls, conceptualized as a “gaze situation”. The gaze situation is characterized by the interaction of four psychological micro-processes that stimulate sexual awareness and the integration of sexual self-experience. The author chooses to conceptualize these micro-processes as a) shifting reactions towards adolescent girls; b) the sense of personal singularity and uniqueness; c) the body becoming an alluring public object; d) striving to repeat the pleasurable experience of being looked at. Two additional themes were discussed as features of the intense I–Other experience related to the growing heterosexual sexual awareness: a) the Other should be a person outside the family, b) the Other should be a person of the opposite sex. Despite some limitations of the study, its findings confine the importance of intersubjective experiences with the other sex to the development of sexual selfhood in adolescence.
Keywords: qualitative hermeneutic research; adolescent girls; sexuality; mirroring; “gaze situation”